Where Africa Meets Asia: Chinese Agricultural and Manufacturing Investment in Madagascar - Yunnan Chen; David G. Landry (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
Madagascar's abundant natural resources, low labor costs, and geographic location make it a potentially attractive destination for Chinese outward investment as rising wages in China and domestic competition increasingly drive firms to "go out." The current wave of Chinese investment in the country may have significant implications for the development and potential transformation of the Madagascan economy, particularly for agriculture and manufacturing. This research finds some evidence of limited technology transfer occurring from Chinese firms in Madagascar, yet currently, Chinese investment remains small in scope, and is also constrained by a problematic policy environment.
Keywords: 330